Social Disclosure and Profitability: Study in Indonesian Companies - Fida Muthia; Isnurhadi Isnurhadi (JEMBATAN, 2019)
We tried to investigate the causal relationship between profitability and corporate social responsibility disclosure.  We choose listed companies under Kompas100 index as our sample to test whether profitability ‘granger cause’ CSR disclosure and whether CSR disclosure ‘granger cause’ profitability. We conduct multiple regression analysis to see the effect. ROA, ROE and NPM are used as the proxy for profitability and the number of lines in sustainability report as the proxy for CSR disclosure.  We find that there is no link between profitability and CSR disclosure and that profitability is not the main reason for company to publish CSR report.  This study is limited to companies listed in Kompas100 index.  The findings of this study can give insights to the managers and investors that there is no link between profitability and CSR disclosure